Optimization of Magnetic Ferotrap Technology Integrated with IoT Sensors as an Effort to Mitigate Microplastics for Increasing Local Farmers' Incometan Income Petani Lokal - Hikmal Akbar Habibie Habibie; Bintang Romadhon Putra Alasyari Alasyari; Nindya Aliyah Maulidina Maulidina; R. Mohammad Alghaf Dienullah Dienullah (Universitas Dehasen Bengkulu, 2026)
Microplastic contamination in irrigation systems threatens soil quality and crop productivity. This study evaluates the potential of FERRO-PLANT, a ferro-magnetic trap integrated with IoT sensors, as a preventive mitigation approach. A qualitative literature review was conducted using secondary data from recent scientific publications, analyzed through content and comparative methods. Results indicate that microplastics reduce soil function and photosynthetic efficiency. FERRO-PLANT offers selective adsorption, real-time monitoring, and microhydro-based energy support. Projections show productivity increases of 8–12% and cost reductions of 10–15%, raising farmer income by 18–27%. The system is promising for sustainable agriculture and food security.